Pengembangan Sistem Informasi 3 Pilar Dalam Penyelesaian Perkara Tilang Di Kota Kediri Menggunakan RESTful Web Service - Pramuditya Ananta Nur; Adam Hendra Barata; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The traffic and the transportation is an unified system which is consist of the traffic, the public transportation, the traffic network, the infrastructure, the vehicles, the drivers, the road user and also it's management. Although there is a certain regulation about the traffic, there are still a lot of traffic violation. The road user or the driver who violate the traffic will get such kind of ticket. The mechanism of the settlement of traffic violation involved three law government institutions. They are Indonesian National Police, Supreme Court of Indonesia and Attorney Office. In Kediri, they create a memorandum of understanding (MoU) which is known as the â€œSurat Keputusan bersama Tiga Pilarâ€ in settlement the traffic violation cases. But there are some problems appear, like data that are not well organized, making reports that take time, the lack of information for the citizens, and also the difficulties in accessing the information to other government institutions in Kediri. Sistem Informasi Tiga Pilar was created using RESTful web service in order to make all of the business process in each institutions become easier. Implementation is done using Spring Boot framework as the web service of the system and AngularJs to connect between client and web service. Testing is done by using validation testing, unit testing, data integrity testing, and usability testing. The result of validation testing and unit testing is 100%, and usability test result with Software Usability Scale (SUS) is 72,5 with effectiveness value 90,9%.